73‐3: Distinguished Student Paper: Full Color Quantum Dot Light‐Emitting Diodes Patterned by Photolithography Technology. Issue 1 (30th May 2018) - Ji, Tingjing; Jin, Shuang; Chen, Bingwei; Huang, Yucong; Huang, Zijing; Chen, Zinan; Chen, Shuming; Sun, Xiaowei
Abstract : Photolithography is a high resolution and mature patterning technique which has been widely used in semiconductor industry. For display application, a pixel consists of red (R), green (G) and blue (B) side‐by‐side sub‐pixels, which thereby requires a high resolution patterning of the light‐emission layers. In this work, photolithography is used to fine pattern the quantum dot (QD) light‐emitting layers. To prevent the QDs being washed off during the lift‐off process, the ZnMgO layer is treated by the hydrophobic material hexamethyldisilazane (HMDS). With HMDS treatment, the adhesion between the QDs and the ZnMgO is effectively improved. As a result, side‐by‐side RGB QD with pixel size 30 μm × 120 μm is successfully achieved. After patterning, the R, G and B QLEDs exhibit a maximum current efficiency of 11.6 cd/A, 29.7 cd/A and 1.5 cd/A, respectively.